The Effect Of Audiovisual Health Promotion Media On Students' Knowledge About HIV/AIDS At Senior High School (SMA) 6 Padang In 2024 - Arifin, Yulia; Hesti, Novria; Hardiyanty, Dicka (International Health Sciences Journal, 2025)
The West Sumatra Provincial Health Office in 2022 found the number of HIV cases to be 751 cases. There was an increase in HIV/AIDS cases in 2022 reaching 864 cases. One of the efforts that can be done to introduce and increase adolescents' knowledge about HIV / AIDS is to provide audiovisual health promotion. The purpose of this study was to determine the effect of the use of health promotion media using audiovisual media on student knowledge about HIV / AIDS SMA Negeri 6 Padang. The type of research used is quantitative research with a pre-experiment research design of one only group pretest and posttest. The place of this research is at SMA N 6 Padang. The population in this study were female students of class XI MIPA with a sample of 71 respondents. Data were analysed univariately and bivariately using the Willcoxon test. There is an increase in knowledge after being given audiovisual health promotion about HIV/AIDS. The p-value (p=0.000) means that there is an effect of the use of audiovisual health promotion media on student knowledge about HIV/AIDS SMA Negeri 6 Padang. The conclusion is that there is an effect of the use of health promotion media using audiovisual media on student knowledge about HIV/AIDS SMA Negeri 6 Padang. It is recommended to the principal to be able to collaborate with health workers through routine counselling in order to increase student knowledge, especially about HIV/AIDS.